Técnicas terapêuticas de fratura mandibular em cães: revisão sistemática - Assunção, Danilla Mendes de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Mandibular fractures in small animals are common and the treatment aims to immobilize the lesion to restore functional mobility of the bone. Thus, this systematic review aimed to identify the most appropriate therapeutic modalities for type of mandibular fracture in dogs. The searches in the databases revealed that in the last 20 years no new techniques appeared, but great advances were made in the development of the materials used in these techniques and in the association of digital technologies with traditional treatments. Traditional models of mandibular fracture therapy in dogs include: muzzles (taping and traditional), interdental fixation and maxillomandibular fixation, intramedullary pin, interdental wire, interfragmentary wire, bony plates, screws and external skeletal fixator. The determination of the therapy depends on the factors: type, location, presence of teeth, dental occlusion, race and age. Digital resources (computerized tomography, 3D printing) and the new types of biodegradable and more resistant materials are highly applicable in the planning of individualized treatments to obtain the best results, but some are still prototypes, without practical application. It was concluded that there is no exact technique for each fracture, since each case has to be analyzed taking into account the factors previously mentioned to use the most effective treatment for a given situation. Often, the association between techniques is the best option. The new types of digital materials and technologies are current trends that will allow to optimize the protocols of treatment of jaw fractures. Furthermore, successful surgery combined with an adequate postoperative period is extremely important for the success of therapy.

As fraturas mandibulares em pequenos animais são comuns e o tratamento visa imobilizar a lesão para restabelecer a mobilidade funcional do osso. Assim, esta revisão sistemática objetivou identificar as modalidades terapêuticas mais adequadas para cada fratura mandibular em cães. As buscas nas bases de dados revelaram que nos últimos 20 anos não surgiram novas técnicas, mas houve grandes avanços no desenvolvimento dos materiais usados nestas técnicas e na associação de tecnologias digitais a tratamentos tradicionais. Os modelos tradicionais de terapêutica de fratura mandibular em cães incluem: focinheiras (de esparadrapo e tradicional), fixação interdentária, fixação maxilomandibular, pino intramedular, fio interdentário, fio interfragmentário, placas ósseas, parafusos e fixador esquelético externo. A determinação da terapêutica depende dos fatores: tipo, localização, presença de dentes, oclusão dentária, raça e idade. Os recursos digitais (tomografia computadorizada; impressão 3D) e os novos tipos de materiais biodegradáveis e mais resistentes são altamente aplicáveis no planejamento dos tratamentos individualizados para a obtenção dos melhores resultados, porém alguns ainda são protótipos, sem aplicação na prática. Concluiu-se que não há uma técnica de escolha para cada fratura, pois cada caso tem que ser analisado, levando em consideração os fatores anteriormente citados, para utilizar o tratamento mais efetivo para determinada situação. Muitas vezes, a associação entre as técnicas é a melhor opção. Os novos tipos de materiais e tecnologias digitais são tendências atuais que permitirão otimizar os protocolos de tratamento de fraturas de mandíbulas. Ainda, uma cirurgia bem-sucedida aliada a um pós-operatório adequado é de extrema importância para o êxito da terapêutica.
Keywords: Tratamento Tratamento; Fraturas maxilomandibulares; Cães; Therapeutic techniques